Democracy and authoritarianism in the Arab world. The evolution of a long debate (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
The representation of the Arab world as ‘exceptional’ (because of an absence of democracy) when compared with other regions of the world has permeated political science debates. Falling in line with Orientalist and culturalist theses, such interpretations read the region’s political evolution as the result of chaos, randomness and external events and view Arab societies as backward and tribal. Over the decades, these readings have become tightly intertwined with studies emphasizing an inevitable clash of civilizations. In this binary contraposition, the Arab world represents an underdeveloped and violent region, largely because of Islam. The interweaving of development and democracy, which started in modernization theory in the 1950s and 1960s, has become even tighter in the era of globalization: Development, especially through the actions and the buzzwords of international organizations such as the World Bank and the International Monetary Fund, increasingly became synonymous with democracy. This paper will unpack the debate by focusing on its key elements. The intent is to show how, even as paradigms and the lexicon change, this debate is still anchored in a stereotypical and primordialist view of the entire region.